Digital Influence: A Review of Husain Basyaiban's Da'wah Through the TikTok Platform - Kurniawan, Andri; Fadilah, Nurul (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
The intelligence of digitalization affects the lifestyle of Muslim youth. The variety of values produced, including negative values such as moral degradation and loss of wisdom in social media behavior (digital), is often witnessed in various statuses and comments. This study aims to analyze Husain Basyaiban's da'wah rhetoric through the TikTok platform in the review of challenges and opportunities in the digital era through Aristotle's rhetoric. The research method used is a qualitative method with a library research approach. The results of this study indicate that Husain Basyaiban uses preaching rhetoric with word selection, language style based on tone, and language style based on sentence structure. Then, use the voice styles of pitch, pause, and rate. Finally, using gestures ranging from appropriate body posture and eye gaze, good appearance, and dress, as well as facial expressions and hand movements that adjust. In addition, some challenges must be faced, such as the bullying attitude of netizens, sensitivity to the environment, balancing education with da'wah content, and the need to be creative. Meanwhile, the opportunity for digital da'wah is that good rhetorical skills can persuade netizens and have implications for the number of followers as a target of da'wah.